2009
DOI: 10.1088/0953-8984/21/46/464108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noise-induced nucleation on grain size distribution studied via the phase-field crystal method

Abstract: We contribute to the more detailed understanding of the phase-field crystal model recently developed by Elder et al (2002 Phys. Rev. Lett. 88 245701), by focusing on its noise term and examining its impact on the nucleation rate in a homogeneously solidifying system as well as on successively developing grain size distributions. In this context we show that principally the grain size decreases with increasing noise amplitude, resulting in both a smaller average grain size and a decreased maximum grain size. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…It seems likely that this is a time range of observation reported in Ref. [11]. At the later times, by contrast, the coarsening dynamics have sped up, and we have in fact found that a higher value of ζ results in a configuration with a larger average domain size.…”
Section: Simulation Results and Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…It seems likely that this is a time range of observation reported in Ref. [11]. At the later times, by contrast, the coarsening dynamics have sped up, and we have in fact found that a higher value of ζ results in a configuration with a larger average domain size.…”
Section: Simulation Results and Discussionsupporting
confidence: 66%
“…In this paper, we will focus exclusively on the case where η is conserved, which is of particular interest in relation to the recent simulation result [11]. We note in passing that the previous work [2,9,10] referred to in the Introduction all focused on the nonconserved version of Eq.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…-dendrites [26][27][28][29][30] -eutectics [26,28,29,31] -homogeneous nucleation [28,[30][31][32][33]] -heterogeneous nucleation [30,31,34,35] -grain-boundary melting [36,37] -fractal growth [38,39] -crystal anisotropy [33,38,[40][41][42][43][44]] -density/solute trapping [38,39,45] -glass formation [35,46,47] -surface alloying [48,49] Colloid patterning [33] Grain-boundary dynamics [50] Crack propagation [50] Elasticity, plasticity, dislocation dynamics [12,[50][51][52][53][54] Kirkendall effect [55] Vacancy transport [56] Liquid phase separation with colloid accumulation at phase boundaries …”
Section: Phenomenamentioning
confidence: 99%
“…For example, in the growth of domains of lamellae from random initial conditions, the addition of a small amount of noise is consistently shown to increase the growth exponent and leads to enhanced pattern orientation with increasing noise strength [43]. In a recent paper [44], an additive noise effect in the disorder-to-hexagonal pattern formation has been studied by simulations of Eq. (10).…”
Section: Summary and Discussionmentioning
confidence: 99%